Uma estimativa interior do gradiente para a equação da curvatura média em variedades riemannianas - Nogueira, José Ivan Mota (2012)
We deduce an interior gradient estimate for the mean curvature equation for Killing graphs in Riemannian manifolds inspired by the normal perturbation technique due to N. Korevaar